2020
DOI: 10.1177/2320206820960862
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Cancer Stem Cells in Vasculogenic Mimicry Formation: A New Dimension for Targeted Therapy

Abstract: Aim: Cancer stem cells (CSCs) or tumor-initiating cells have self-renewal and uncontrolled tumor growth capacity that promotes metastasis and recurrence. Challenges in anticancer have found a lateral dimension of treatment against a new pattern of tumor microcirculation, known as vasculogenic mimicry (VM), involved in cancer progression. Increasing evidence suggest that CSCs are involved in the formation of VM. In this review the correlation between CSCs and VM formation is been enlightened. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Additionally, preclinical pharmacological studies have shown that VM is connected to anticancer therapy resistance [83]. A significant amount of data suggests that CSCs aid in the development of VM (Figure 1H) [84]. The VM phenotype of tumour cells has a molecular signature that includes upregulated expression of genes related to embryonic progenitors, endothelial cells, vessel formation, matrix remodelling, and coagulation inhibitors, as well as downregulated expression of genes primarily related to lineage-specific phenotype markers [80,85].…”
Section: Vasculogenic Mimicrymentioning
confidence: 99%
“…Additionally, preclinical pharmacological studies have shown that VM is connected to anticancer therapy resistance [83]. A significant amount of data suggests that CSCs aid in the development of VM (Figure 1H) [84]. The VM phenotype of tumour cells has a molecular signature that includes upregulated expression of genes related to embryonic progenitors, endothelial cells, vessel formation, matrix remodelling, and coagulation inhibitors, as well as downregulated expression of genes primarily related to lineage-specific phenotype markers [80,85].…”
Section: Vasculogenic Mimicrymentioning
confidence: 99%